W kierunku ergonomii widzenia - Leszkowicz, Mateusz (Kultura-Społeczeństwo-Edukacja, 2023)
Active vision is essential for understanding visual content, with particular emphasis on materials and media designed specifically for understanding the world. Contemporary texts and media messages are becoming clearly atomized, divided into smaller fragments and are becoming strongly related to the graphic form. The article will discuss several graphic treatments that direct the recipient’s attention and facilitate visual thinking.